AN EVALUATION OF VISUAL PRIVACY LEVEL IN RESIDENTIAL UNIT'S LAYOUTS IN KHARTOUM, SUDAN - Maysa Abubaker Yousif; Aniza Abdul Aziz (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2021)
Visual privacy is one of the vital aspects of Islamic house designs. This paper aimed to analyze the level of visual privacy in the layout of different residential apartment unit samples in Khartoum, Sudan based on Islamic values and Sudanese culture and how modern apartment unit designs respond to these needs. Models included four units from courtyard-villas and two units from apartment buildings. The architectural layout plans, spatial relation, functions, and space zoning were applied to assess the level of visual privacy of each unit. Findings showed that the courtyard-villas had a higher degree of privacy and cultural values, reflecting more of the Sudanese lifestyle than the apartment units, even though the design of the apartment units pays more attention to the nuclear family privacy. This study would assist designers in enhancing the visual privacy in apartment unit layouts by highlighting factors that diminish or enhance the visual privacy level to create appropriate designs for Sudanese Muslims and Muslims in general.